Facile Synthesis of Water-Soluble Rhodamine-Based Polymeric Chemosensors via Schiff Base Reaction for Fe3+ Detection and Living Cell Imaging - Qiu, Xiaoyong; Huang, Jun; Wang, Ning; Zhao, Kaijie; Cui, Jiwei; Hao, Jingcheng (Frontiers in Chemistry, 2022)
Quantitative and accurate determination of iron ions play a vital role in maintaining environment and human health, but very few polymeric chemosensors were available for the detection of Fe3+ in aqueous solutions. Herein, a water-soluble rhodamine-poly (ethylene glycol) conjugate (DRF-PEG), as a dual responsive colorimetric and fluorescent polymeric sensor for Fe3+ detection with high biocompatibility, was first synthesized through Schiff base reaction between rhodamine 6G hydrazide and benzaldehyde-functionalized polyethylene glycol. As expected, the introduction of PEG segment in DRF-PEG significantly improved the water solubility of rhodamine derivatives and resulted in a good biosensing performance. The detection limit of DRF-PEG for Fe3+ in pure water is 1.00 μM as a fluorescent sensor and 3.16 μM as a colorimetric sensor at pH 6.5. The specific sensing mechanism of DRF-PEG toward Fe3+ is proposed based on the intramolecular charge transfer (ICT) mechanism, in which the O and N atoms in rhodamine moiety, together with the benzene groups from benzaldehyde-modified PEG segment, participate in coordination with Fe3+. Furthermore, DRF-PEG was applied for the ratiometric imaging of Fe3+ in HeLa cells and showed the potential for quantitative determination of Fe3+ in fetal bovine serum samples. This work provides insights for the design of water-soluble chemosensors, which can be implemented in iron-related biological sensing and clinical diagnosis.